Dual Rotor PMFSM for Counter-Rotating Wind Turbine - Lutpi, Mohd Hanif; Jenal, Mahyuzie (Evolution in Electrical and Electronic Engineering, 2023)
A wind turbine consists of a turbine rotor installed for wind rotation that has many blades that convert the energy in the wind into rotational energy. Wind turbines consist of two sets of counter-rotating rotors leading to twice the power density. Flux Switching Machine (FSM) is one of the new categories of electric motors developed by previous researchers and has become popular for electrical AC motor applications. Permanent Magnetic Flux Switch Machine (PMFSM), Field Excitation Flux Switch (FEFSM), and Hybrid Excitation Flux Switch are the three types of FSM (HEFSM). One of these is PMFSM, which offers advantages such as low cost, simple construction, and FEC-free winding that obtains minimal copper loss—suitable for diverse performances. This work presents a design study and investigative analysis of a PMFSM twin rotor with rotor poles for counter-rotating wind turbines. Diverse permanent magnet flux switching range devices are available in terms of design (PMFSM). PMFSM with segmented permanent magnet PM consequent pole arrangement, on the other hand, is intensively researched. Moreover, PMFSM is examined with several rotor positions, including inner and exterior rotors. To achieve motor performance in terms of torque, power, and speed, a dual rotor arrangement with varied stator configurations is used. Dual rotors have been a popular issue in the field of electrical machine research because they offer a twin-rotor configuration to boost output torque and power. Yet, when torque and power increased, other motor characteristics, such as back-EMF, worsened, resulting in higher-order harmonic content. Finally, at the end of this chapter, all of the findings from the research will be summarized.